If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+9=18/7
We move all terms to the left:
6x+9-(18/7)=0
We add all the numbers together, and all the variables
6x+9-(+18/7)=0
We get rid of parentheses
6x+9-18/7=0
We multiply all the terms by the denominator
6x*7-18+9*7=0
We add all the numbers together, and all the variables
6x*7+45=0
Wy multiply elements
42x+45=0
We move all terms containing x to the left, all other terms to the right
42x=-45
x=-45/42
x=-1+1/14
| 9=64y/3*24 | | 7+15x=52 | | 5(3)-1-x-2=2(3)+4 | | 30+12x=54 | | 8=3(v+-1)+5 | | -1/3(x-5)(x-5)=0 | | 1.65(b+1)+1.6=9.85 | | 5x-1/2-x-2/6=2x+4/3 | | 7y3+27y2=40y | | 12x+20=210 | | 116+20r=2r^2 | | 1.76+y=5.4 | | 20a+6=10a-7 | | 1.9+y=3.62 | | 3^(-2n+1)=9 | | 4(x-6)=6(x+5) | | 4(x-6)=6(x=5) | | 1/2(8x+30)=9x-5 | | 6=2/3m-2 | | x+x+6=-28 | | A=2x-80 | | 0.14y=3.36 | | 1/2(4x+8)=6x+12 | | 3x+200=2x | | (5x-48)/7=3x | | 18=11+-c | | 2(3x+1)=4(-2x-7) | | -3=-3(y-9) | | 4x-10=3x-3-4 | | y+0.69=2.7 | | 8a+3a=5+3a | | 5.24=2.62(r-12) |